Performance of the forensic psychologist on parental alienation - Faverzani da Luz, Ariele; Gelain, Denise; Kochenborger Benincá, Tatiana (Revista de Psicologia da IMED, 2014)
The performance of the psychologist in the family area is wide and covers a number of issues, including the cases where it turns out the parental alienation. In this sense, this article aims to reflect on the importance of the performance of forensic psychology in Family Law, in particular, on the issue of parental alienation. And as specific objectives to investigate what measures taken after your diagnosis, understand the behavior and characteristics of alienadores and check out their consequences in children and adolescents victimised. This research consists of a survey of exploratory nature, carried out with six psychologists operating in Judiciary of Rio Grande do Sul (Brazil) through a questionnaire with questions semi open submitted by e-mail. The data were organized and systemized according to the goals, using the method of Bardin’s Analysis Content. The survey results showed an appreciation of the work of the psychologist in the sticks of Legal Family and a knowledge of the aspects of parental alienation on the part of professionals, contributing to the adoption of appropriate measures to combat it.